2021
DOI: 10.1159/000514273
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Bromelain and Acetylcysteine (BromAc®) for Pleural Involvement in Pseudomyxoma Peritonei

Abstract: Pseudomyxoma peritonei (PMP) is a rare mucinous disease most commonly arising from the appendix. Pleural involvement arising from established PMP is seen in a small number of cases. Combined cytoreductive surgery and hyperthermic intrathoracic chemotherapy is the treatment of choice when managing intra-thoracic PMP. In cases of recurrence, surgical intervention may be technically challenging and carry higher rates of complications, morbidity, and mortality. Bromelain and acetylcysteine (BromAc<sup>®</… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Tumors with soft or intermediate textures are more susceptible to the drug's action. In the first two cases reported, effectively, large response differences were reported, possibly due to the tumor consistency (Lam et al, 2021). The safety profile was however good as also the objective response.…”
Section: Clinical Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Tumors with soft or intermediate textures are more susceptible to the drug's action. In the first two cases reported, effectively, large response differences were reported, possibly due to the tumor consistency (Lam et al, 2021). The safety profile was however good as also the objective response.…”
Section: Clinical Studiesmentioning
confidence: 94%
“…The anti-cancer properties of bromelain, in combination with N-acetylcysteine, were used also to produce a new drug (BromAc ® ) which has been recently proved effective in the recurrent thoracic pseudomyxoma peritonei (PMP) treatment ( 154 ). According to the bromelain-based mucus-disrupting activity (see above), the mucolytic properties of BromAc ® help the tumor dissolution when it was injected directly into mucinous disease.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Bromelain, a complex mixture of proteolytic cysteine proteases obtained from stem of pineapple (Ananas comosus) is a food supplement exhibiting a variety of pharmacological activities. Various studies substantiate the bromelain's mucolytic [13], wound healing [14], fibrinolytic [15], antiedematous [16], antithrombotic [17], anti-inflammatory [18], antioxidant [19], anticancer [20] as well as immunomodulatory activity [21]. Bromelain significantly decreases COX-2 and PGE-2 expression and lower the cytokines (IL-1β, IL-6 and TNF-α) secretion from immune cells in inflammatory conditions [22,23].…”
Section: Introductionmentioning
confidence: 94%
“…Ghensi et al [55] concluded from their study that dexamethasone sodium phosphate (20 ng/mL) when added to bromelain (20 ng/mL) activated a greater number of mesenchymal stem cells, resulting in increased hyaluronan and collagen synthesis as well as the release of anti-inflammatory cytokines. Lam et al [56] found that bromelain and acetylcysteine (BromAc) is a newer therapeutic medication that has been shown to have mucolytic characteristics. It aids tumor dissociation and enables for swallowing when injected directly into mucinous illness.…”
Section: Synergistic Effects Of Bromelainmentioning
confidence: 99%